The Effect Of Regional Expenditures And Economic Growth On The Human Development Index (IPM) - Fanji Farman (Journal of Business, Accounting and Finance, 2022)
The Human Development Index (IPM) is an important indicator to measure success in efforts to build the quality of human life (community/population). This study aims to find out that there is no effect of shopping areas and economic growth on the human development index (HDI) in Sumedang Regency in 2015-2019. This research is a panel data with data processing techniques using multiple linear regression methods, namely the classical assumption test, the coefficient of determination and hypothesis testing with the help of SPSS 23.0 software. Data sources come from various sources, including the website of the Central Statistics Agency and the website of the Directorate General of Fiscal Balance. The results of this study indicate that simultaneously the regional expenditure variables and economic growth have a significant effect on the Human Development Index in Sumedang Regency in 2015-2019 and the regression results show that 98.9% of the variation in the independent variables can explain the Human Development Index variable in Sumedang Regency while the rest of 1.1% is influenced by other factors that are not included in the variables of this study. Partially the regional expenditure variable (X1) has no positive and significant effect on the Human Development Index (Y) in Sumedang Regency, while economic growth (X2) has a significant effect on the Human Development Index in Sumedang Regency in 2015-2019.